Study of kinematic viscosity and density of biodiesels exposed to radiations. (2021) - Sarin, Amit; Sharma, Neerja; Devgan, Kusam; Singh, Meetu
Abstract: The storage of biodiesels is a major concern for its long term performance. The present work reports the kinematic viscosity and density of Jatropha biodiesel (JBD) and Pongamia biodiesel (PBD) when exposed to sunlight and ultraviolet (UV) irradiation for up to thirty days and ten hours respectively. Along with the exposure towards radiations, different antioxidants viz. Butylatedhydroxyanisole (BHA), Butylatedhydroxytoluene (BHT), Tert-butyl hydroquinone (TBHQ) were also added to the biodiesel samples to observe their impact along with varying storage ambiance. The study aimed to establish a concrete approach towards the stability of biodiesels when exposed to the diverse ambiance.